2004
DOI: 10.1016/j.femsim.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in regulation of inflammatory response to influenza a virus and endotoxin in suckling rat pups: a potential relationship to sudden infant death syndrome

Abstract: Data increasingly implicate a possible role of immune and inflammatory responses to infection in sudden infant death syndrome (SIDS). We have previously described a dual challenge model that results in pathology, organ damage, vascular collapse and unexplained death similar to that seen in SIDS. In this study, we examined changes in inflammatory cytokine mRNA in the lung and liver and regulation of pathways associated with nitric oxide production. Our data suggest that priming of the immune system by mild vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…prone sleeping position) with genetic risk factors (related to immune/infectious responses) could increase the risk of SIDS through unknown underlying mechanisms. Different hypotheses have been postulated as pathogenic and/or associated events for SIDS in regard to asymptomatic virus infection: molecular mimicry, inflammatory-related proteins [8,9], an increase in the activity of bacterial toxins [21], or some kind of immune disregulation (e.g., in an animal model similar to SIDS, asymptomatic viral infection has been suggested that it can boost the effect of non-lethal doses of endotoxin, resulting in an increased nitric oxide synthase production) [22]. However, the intrinsic mechanisms related with these findings remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…prone sleeping position) with genetic risk factors (related to immune/infectious responses) could increase the risk of SIDS through unknown underlying mechanisms. Different hypotheses have been postulated as pathogenic and/or associated events for SIDS in regard to asymptomatic virus infection: molecular mimicry, inflammatory-related proteins [8,9], an increase in the activity of bacterial toxins [21], or some kind of immune disregulation (e.g., in an animal model similar to SIDS, asymptomatic viral infection has been suggested that it can boost the effect of non-lethal doses of endotoxin, resulting in an increased nitric oxide synthase production) [22]. However, the intrinsic mechanisms related with these findings remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, susceptibility to sudden death in this model was also dependent on the age of the animal. 11,12 Evidence indicated that the death of the rats was due to rapid systemic shock. Endotoxin is known to lower blood pressure and cause shock.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NO expression has been found to be associated with organ damage described in autopsy reports of infants who died of SIDS. NOS mRNA up-regulation has been observed after endotoxin administration in animal models for the study of SIDS (13,14).In vitro and in vivo studies indicated that NO has inhibitory properties at the carotid body and that eNOS is primarily responsible for this effect (15,16). Administration of NO donors to the carotid body reduces its chemosensory response to a decrease in oxygen concentration (16).…”
mentioning
confidence: 99%
“…Elevated NO expression has been found to be associated with organ damage described in autopsy reports of infants who died of SIDS. NOS mRNA up-regulation has been observed after endotoxin administration in animal models for the study of SIDS (13,14).…”
mentioning
confidence: 99%